2022
DOI: 10.1172/jci159500
|View full text |Cite
|
Sign up to set email alerts
|

Favorable vaccine-induced SARS-CoV-2–specific T cell response profile in patients undergoing immune-modifying therapies

Abstract: BACKGROUND Patients undergoing immune-modifying therapies demonstrate a reduced humoral response after COVID-19 vaccination, but we lack a proper evaluation of the effect of such therapies on vaccine-induced T cell responses. METHODS We longitudinally characterized humoral and spike-specific T cell responses in patients with inflammatory bowel disease (IBD), who were on antimetabolite therapy (azathioprine or methotrexate), TNF inhibitors, and/or other biologic treatmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Importantly, in vaccinees where their Spike-specific T cell response was significantly inhibited by the mutations present in Omicron, their combined vaccine-induced T cell response (Spike, Membrane and Nucleoprotein) was better preserved against Omicron (Figure 7C). The presence of multi-protein specific T cells in individuals vaccinated with inactivated virus can therefore provide them with a population of memory T cells more likely to tolerate the frequently found amino acid substitutions in Spike which can partially suppress the Spike-specific T cell response elicited by current Spike mRNA vaccines 4248 . While the ability of Omicron to escape the full repertoire of Spike-specific T cells induced by mRNA vaccines occurs only in a minority of individuals (10-15%), immune escape can be substantial in particular for Spike-specific CD8 T cells 48 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, in vaccinees where their Spike-specific T cell response was significantly inhibited by the mutations present in Omicron, their combined vaccine-induced T cell response (Spike, Membrane and Nucleoprotein) was better preserved against Omicron (Figure 7C). The presence of multi-protein specific T cells in individuals vaccinated with inactivated virus can therefore provide them with a population of memory T cells more likely to tolerate the frequently found amino acid substitutions in Spike which can partially suppress the Spike-specific T cell response elicited by current Spike mRNA vaccines 4248 . While the ability of Omicron to escape the full repertoire of Spike-specific T cells induced by mRNA vaccines occurs only in a minority of individuals (10-15%), immune escape can be substantial in particular for Spike-specific CD8 T cells 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of multi-protein specific T cells in individuals vaccinated with inactivated virus can therefore provide them with a population of memory T cells more likely to tolerate the frequently found amino acid substitutions in Spike which can partially suppress the Spike-specific T cell response elicited by current Spike mRNA vaccines [42][43][44][45][46][47][48] . While the ability of Omicron to escape the full repertoire of Spike-specific T cells induced by mRNA vaccines occurs only in a minority of individuals (10-15%), immune escape can be substantial in particular for Spike-specific CD8 T cells 48 .…”
Section: The Importance Of Eliciting a Multi-antigenic T Cell Respons...mentioning
confidence: 99%
See 1 more Smart Citation
“…Production of neutralizing antibody was evidenced even when they were tested against virus variants ( 65 ). Poor impact of variants on immune response to mRNA vaccines in IBD patients seems confirmed by the evidence that in subjects receiving antimetabolite therapy (azathioprine or methotrexate), TNF inhibitors and/or other biologic treatment (anti-integrin or anti-p40) for up to 6 months after completing two-dose COVID-19 mRNA vaccination a favorable profile of vaccine-induced T cell responses was found, despite they were infected by the omicron variant ( 74 ).…”
Section: Immune Response Of Patients With Inflammatory Bowel Disease ...mentioning
confidence: 90%
“…Data on patients with inflammatory bowel disease (IBD) treated with high doses of systemic corticosteroids, infliximab, or infliximab and immunomodulators showed that they present a blunted response to the anti-SARS-CoV-2 vaccination [ 133 ]. However, a study on humoral and spike-specific T cell responses in patients with IBD who were on antimetabolite therapy (azathioprine or methotrexate), TNF inhibitors, and/or other biologic treatment (anti-integrin or anti-p40) for up to 6 months after completing two-dose COVID-19 mRNA vaccination showed that a spike-specific T cell response was not only induced in treated patients with IBD at levels similar to those of healthy individuals, but also was sustained at a higher magnitude for up to 6 months after vaccination, particularly in those treated with TNF inhibitor therapy [ 134 ].…”
Section: Immune Response To Sars-cov-2 Vaccinationmentioning
confidence: 99%